Postpartum Mothers' Behavior Regarding Perennial Wound Care At The Murniati Clinic - Fauziah Gusvita Syarah; Mahyunidar, Mahyunidar; Ilma Widiya Sari; Luluk Khusnul Dwihestie (Jurnal EduHealth, 2024)
Opening oferlukaan the jalan birth canal in the puerperium occurs in almost 90% of childbirth, either with or without episiotomy. The incidence luka pereniof Maple wound in ibu maternity capital in the world in 2015 there were 2.7 million cases, where this figure is expected to reach 6.3 million by 2050. Based on an initial survey conducted by researchers in May to June 2022, it was found that as many as 12 postpartum mothers experienced perenium injuries at the Murniati Kisaran Clinic. Perineal care is the fulfillment of the need to nourish the area between the thighs bounded by the vulva and anus in mothers who are in the period between the birth of the placenta until the return of the genital organs as in the time before pregnancy. The purpose of perenium wound care for women after childbirth is to reduce discomfort , manan, prevent infection, and promote healing. (Morison, 2003). The design of this study is bersifat descriptive , namely to describe how the behavior ibu of postpartum mothers towards perawatan luka perenium wound care at the Murniati Clinic in the range of 2018. By sampling the total sampling of the entire population was used as a sample of 37 puerperal mothers with perenium wounds. Based on the results of the study, it was found that the behavior of puerperal mothers in performing perenium wound treatment at the Murniati clinic in the 2018 Range was sufficient, namely as many as 23 respondents (62%), sufficient knowledge, namely as many as 23 respondents( 62%), sufficient attitude, namely as many as 17 respondents (46%), and sufficient action, namely as many as 20 respondents (35%). The suggestions that can be given on the issue include that the mother always do perenium wound care during the puerperium in order to accelerate the healing process of the wound.